2014
DOI: 10.1111/ped.12234
|View full text |Cite
|
Sign up to set email alerts
|

Two outbreaks of ESBL‐producing Klebsiella pneumoniae in a neonatal intensive care unit

Abstract: The deficiencies in the infection control measures in an NICU may transform into an epidemic rapidly. Therefore, periodic training, observation, and monitoring of compliance are important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…pneumoniae, in particular ESBL-producing strains, is an important cause of nosocomial infections in humans worldwide (Podschun and Ullmann, 1998;Marra et al, 2006;EFSA, 2011;Sumer et al, 2014). For Indonesia, an increase of ESBLs within clinical isolates of K. pneumoniae has been reported in recent years (Herwana et al, 2008, Kuntaman et al, 2011Parwati et al, 2012;Saharman and Lestari, 2013).…”
Section: Introductionmentioning
confidence: 95%
“…pneumoniae, in particular ESBL-producing strains, is an important cause of nosocomial infections in humans worldwide (Podschun and Ullmann, 1998;Marra et al, 2006;EFSA, 2011;Sumer et al, 2014). For Indonesia, an increase of ESBLs within clinical isolates of K. pneumoniae has been reported in recent years (Herwana et al, 2008, Kuntaman et al, 2011Parwati et al, 2012;Saharman and Lestari, 2013).…”
Section: Introductionmentioning
confidence: 95%
“…The eligible studies were undertaken in 30 NICUs in 15 locations. Nineteen (63%) came from high income countries, 3 21 four (13%) from upper-middle income countries, 22 25 six (20%) from lower-middle income countries 26 – 31 and one (3%) from a low income country. 32 Six studies reported Methicillin-resistant Staphylococcus aureus (MRSA).…”
Section: Resultsmentioning
confidence: 99%
“…The source of the outbreak was identified in 17 studies: a patient transferred in from another hospital (6/17) 6 , 7 , 23 25 , 29 ; healthcare worker (4/17) 13 , 19 , 28 , 30 ; contaminated ventilator equipment (5/17) 9 , 16 , 21 , 31 and mothers colonized on surface swabs (2/17). 4 , 26 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, most of the data have not allowed us to identify the modes of acquisition and to consider the best control policies. Indeed, the most frequent published reports regarding the risk factors of infection or colonization by ESBL-PE bacteria were from NICUs 9 , 15 19 , and little is known about factors associated with spreading in the community. Most reports often describe single-unit outbreaks 16 , 17 , 20 and health care-related risk factors.…”
Section: How To Control the Risk Of Transmissionmentioning
confidence: 99%